How ready are communities to implement actions to improve diets of adolescent girls and women in urban Ghana? - Rebecca Pradeilles; Colette Marr; Amos Laar; Michelle Holdsworth; Francis Zotor; Akua Tandoh; Senam Klomegah; Nathaniel Coleman; Kristin Bash; Mark Green; Paula L. Griffiths (BMC, 2019)
Abstract Background Ghana has reached an advanced stage of nutrition transition, contributing to an increase in nutrition-related non-communicable diseases, particularly amongst urban women. Community involvement is an important factor in the success of efforts to promote healthy eating. The readiness of populations to accept a range of interventions needs to be understood before appropriate interventions can be implemented. Therefore, this study assessed how ready urban communities are to improve diets of women of reproductive age in Ghana. Methods Using the Community Readiness Model (CRM), in-depth interviews were conducted with 24 key informants from various sectors in low income communities across two cities in Ghana: Accra and Ho. The CRM consists of 36 open questions addressing five readiness dimensions (community knowledge of efforts, leadership, community climate, knowledge of the issue and resources). Interviews were scored using the CRM protocol with a maximum of 9 points per dimension (from 1 = no awareness to 9 = high level of community ownership). Thematic analysis was undertaken to gain insights of community factors that could affect the implementation of interventions to improve diets. Results The mean community readiness scores indicated that both communities were in the "vague awareness stage" (3.35 ± 0.54 (Accra) and 3.94 ± 0.41 (Ho)). CRM scores across the five dimensions ranged from 2.65-4.38/9, ranging from denial/resistance to pre-planning. In both communities, the mean readiness score for 'knowledge of the issue' was the highest of all dimensions (4.10 ± 1.61 (Accra); 4.38 ± 1.81 (Ho)), but was still only at the pre-planning phase. The lowest scores were found for community knowledge of efforts (denial/resistance; 2.65 ± 2.49 (Accra)) and resources (vague awareness; 3.35 ± 1.03 (Ho)). The lack of knowledge of the consequences of unhealthy diets, misconceptions of the issue partly from low education, as well as challenges faced from a lack of resources to initiate/sustain programmes explained the low readiness. Conclusions Despite recognising that unhealthy diets are a public health issue in these urban Ghanaian communities, it is not seen as a priority. The low community readiness ratings highlight the need to increase awareness of the issue prior to intervening to improve diets.